2017
DOI: 10.1017/9781316440612
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Mobility and Place in Ancient Italy

Abstract: Migration, Mobility and Place in Ancient Italy challenges prevailing conceptions of a natural tie to the land and a demographically settled world. It argues that much human mobility in the last millennium BC was ongoing and cyclical. In particular, outside the military context 'the foreigner in our midst' was not regarded as a problem. Boundaries of status rather than of geopolitics were those difficult to cross. The book discusses the stories of individuals and migrant groups, traders, refugees, expulsions, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(17 citation statements)
references
References 234 publications
0
13
0
4
Order By: Relevance
“…Also, only a few of the small rural sites have been excavated and studied in detail. We should not rule out the possibility that migrants were among the incomers to the Canusine countryside, given the historical evidence for mass migration in third-and second-century BCE Italy (see Isayev 2017). To take one example, in 177 BCE, 4000 Samnite and Paelignian families are said to have moved to the Latin colony at Fregellae (Livy 41.8.8;Isayev 2017, pp.…”
Section: Approaching Displacement and Mobility: The Archaeological Evmentioning
confidence: 99%
“…Also, only a few of the small rural sites have been excavated and studied in detail. We should not rule out the possibility that migrants were among the incomers to the Canusine countryside, given the historical evidence for mass migration in third-and second-century BCE Italy (see Isayev 2017). To take one example, in 177 BCE, 4000 Samnite and Paelignian families are said to have moved to the Latin colony at Fregellae (Livy 41.8.8;Isayev 2017, pp.…”
Section: Approaching Displacement and Mobility: The Archaeological Evmentioning
confidence: 99%
“…In the surviving writings of the ancient inhabitants who lived around the Mediterranean, there is little interest in human mobility as a topic in itself. Migration as a general phenomenon does not appear as a matter of concern, either in terms of security or for the purposes of management and control (Isayev 2017a). Perhaps this is not surprising, considering the novelty of our modern conception of immigration-understood as a move across a national border for the purpose of permanent residence-which only took hold in the early 1800s (Shumsky 2008;Th ompson 2003: 195).…”
Section: Ancient Contextsmentioning
confidence: 99%
“…But mobility in itself was not articulated as a distinct entity separate from the practices of the everyday. Scholarship has shown that in the ancient world it was recognized as being ongoing and cyclical (Horden and Purcell 2000;Isayev 2017a;Tacoma 2016). Hence, we struggle to fi nd any single term either in Ancient Greek or in Latin that categorizes all those on the move in the same way as the current usage of "migrant" does in English.…”
Section: Ancient Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Ao invés de simples inconsistência, esse emprego incongruente de nomes étnicos em Lívio e Estrabão pode ser uma indicação de como as "fronteiras étnicas" na Itália deslocaram-se e reformularam-se ao longo dos últimos quatro séculos a.C. (Isayev, 2007;Scopacasa, no prelo).…”
Section: Territórios E Fronteirasunclassified